Das Urteil des Paris. Eine ikonologische Untersuchung des Paris-Mythos in den Niederlanden des 17. Jahrhunderts - Kopp, Laura (KIT Scientific Publishing, 2017)
After Paris' awakening as judge, the legend finds its way into various literary genres. The papers are unanimous that they hold lessons for the reader. Therefore, the duplex sententia is assigned to the picturesque testimony. The artists, however, found their own ways of hinting the observer to the multiple layers of meaning. Simultaneously the value of didactic function of portraits from the 17th c. has to be relativized, as the eroticism made a significant contribution to the popularization.